2017
DOI: 10.1149/2.0381704jes
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of the Phase and Stress Evolution during Initial Lithiation of Sn Electrodes

Abstract: We have measured the phase kinetics and stress evolution during potentiostatic lithiation of Sn thin film layers to form the first lithiated phase (Li 2 Sn 5 ). Real-time measurements of the wafer curvature are used to determine the stress evolution during lithiation; the corresponding layer structure is determined from the measured charge and confirmed with cross-sectional focused-ion beam (FIB) images and X-ray diffraction (XRD). Prior to new phase formation, a 20-hour conditioning step is used to form a sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 29 publications
2
20
0
Order By: Relevance
“…In the previous work, 2 we reported that the low strain-rate yield stress of Li 2 Sn 5 is around −29 MPa. We also observed the tensile contribution with a value of 8.8 MPa-μm from the SEI at the anode surface.…”
Section: S(t) Dtmentioning
confidence: 84%
See 2 more Smart Citations
“…In the previous work, 2 we reported that the low strain-rate yield stress of Li 2 Sn 5 is around −29 MPa. We also observed the tensile contribution with a value of 8.8 MPa-μm from the SEI at the anode surface.…”
Section: S(t) Dtmentioning
confidence: 84%
“…Further details of the sample fabrication have been described in the previous report. 2 The cells were built and operated in an Ar-filled glove box. In order to distinguish the charge consumed by SEI formation and lithiation as much as possible, the anodes were first processed to grow a SEI layer at 0.8 V vs. Li/Li + for 20 hours before growth of the lithiated Sn phase.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, truek increases linearly with β truec . However, as far as currently known, experimentally measured deformation changes nonlinearly with Li concentration ,,. Furthermore, the variable nature of the elastic modulus of the active layer during electrochemical processes has been experimentally proven ,.…”
Section: Electrochemical Stress Model Of Bilayer Electrode: Modified mentioning
confidence: 99%
“…These investigators applied MOSS to measure the deformation and stress of various electrodes during electrochemical lithiation and delithiation cycles, such as those of Si, graphite, Ge, Sn, and Li 1+ x Mn 2 O 4 . The values of compressive or tensile stresses in different electrodes or of various thicknesses exhibited great differences and showed different trends with capacity ,. However, this technology requires a thick wafers about 500∼1000 um as a measurement basis, therefor fails to characterize the stress in a current collector which is also important.…”
Section: Introductionmentioning
confidence: 99%